2020
DOI: 10.1371/journal.pone.0233884
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 is overexpressed in breast cancer associated with estrogen response and epithelial-mesenchymal transition gene sets

Abstract: Ion channels form an important class of drug targets in malignancies. Transient receptor potential cation channel subfamily M member 4 (TRPM4) plays oncological roles in various solid tumors. Herein, we examined TRPM4 protein expression profile by immunohistochemistry (IHC) in breast cancer cases compared with normal breast ducts, its association with clinico-demographical parameters, and its potential function in breast cancers by Gene Set Enrichment Analysis (GSEA). Data-mining demonstrated that TRPM4 transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 77 publications
3
29
0
Order By: Relevance
“…TRPM4 expression levels have been investigated in a number of different cancers ( Figure 2 ) [ 32 , 33 , 34 , 38 , 39 , 40 , 41 , 101 , 102 , 103 , 104 , 105 , 106 ]. In most studies, TRPM4 protein expression levels were reported to be increased in tumor samples compared to healthy tissue.…”
Section: Trpm4 Expression In Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…TRPM4 expression levels have been investigated in a number of different cancers ( Figure 2 ) [ 32 , 33 , 34 , 38 , 39 , 40 , 41 , 101 , 102 , 103 , 104 , 105 , 106 ]. In most studies, TRPM4 protein expression levels were reported to be increased in tumor samples compared to healthy tissue.…”
Section: Trpm4 Expression In Cancermentioning
confidence: 99%
“…In two recent studies, TRPM4 was reported to be upregulated in breast cancer samples at both the mRNA and protein levels [ 39 , 40 ]. TRPM4 mRNA was significantly upregulated in breast cancer tissue compared to normal breast tissue [ 39 ].…”
Section: Trpm4 Expression In Cancermentioning
confidence: 99%
See 3 more Smart Citations